The Housing of the working people, prepared under the direction of Carroll D. Wright,... by E. R. L. Gould, - Gould, Elgin Ralston Lovell
8th special report of the commissioner of labor. House of Representatives. 53d congress, 3rd session. Ex. doc. n° 354. - The Executive documents of the House of Representatives for the 3rd session of the 53rd congress, 1894-95. Vol. 34